Escalas concorrentes para a mensura????o de personalidade de marca no esporte: um estudo dos clubes de futebol no contexto brasileiro - Santos, Hermes Augusto Batista Mendes (2015)
The positive performance and the success of sports clubs nowadays are not confined to their sports performance, it is also linked to their economic success. The opportunities of a club gains can come from various means, including the association of its brand and their sponsors to marketable products or services. The Personality of the Brand is the relationship between a human personality and a brand personality. It can also be seen as a human personality trait applied to a brand. This study aims to test two scales of measurement of the construct Brand Personality in Sport, the Tsiotsou (2012) and the Schade, Piehler and Burmann (2014), and their influence on declared loyalty and positive word of mouth as dependent variables . Data collection was made through an online survey. To analyze the data it was used Structural Equation Modeling Technique. It was achieved a sample of 301 respondents. It was found that the scale Tsiotsou (2012) gave the best predictive results regarding the dependent variables of the study. It is expected that the results of this study can increase the subject knowledge and be useful to researchers and marketers in the context of sport.